Estudio de la construcción y proyección de la imagen de Daniel Noboa a la presidencia del Ecuador en las elecciones del 2023: Estrategias de la comunicación política y su impacto en la opinión pública en la provincia de Loja. - Briceño Ontaneda, Nasheli Morelia (2024)
This research focused on analyzing the construction and projection of Daniel Noboa's image during his presidential campaign for the 2023 elections. The study specifically focused on the political communication strategies implemented by his campaign team and its effect on public perception in Loja province. The research is of a mixed nature, where quantitative and qualitative techniques were used to determine how these strategies were designed and executed and to influence the opinion of Lojan voters, as well as to examine the verbal communication, non-verbal communication, image positioning and political discourse used by Noboa in the debate of the first and second round of elections. Once the surveys applied to Lojan citizens, the interviews to experts in political communication and the observation of the debates were analyzed, it was determined that 91% of those surveyed responded that Noboa's image did influence their voting decision due to it generated confidence and credibility. In addition, it was established that the most predominant political communication strategy in Noboa's campaign is the use of social networks and the key campaign message is economic development. Finally, the experts in political communication determined that the most effective tools to disseminate Noboa's message and proposal among the voters of the province of Loja was the use of social networks specifically TikTok, they also mentioned that the most effective political communication strategies implemented during his campaign was his exposure in the debate and showing himself away from conflicts. The conclusions highlight the importance of knowing how to communicate efficiently since everything communicates from gestures, posture, facial expressions and clothing in order to consolidate the positioning of the political image. Keywords: Image, Political communication strategies, Debate, Public perception.